(untitled) (Latakia University Journal -Basic Sciences Series, 2017)
يهدف هذا البحث إلى دراسة مسألة رتبة زمرة صفوف تكافؤ الايديالات للحقول التربيعية الحقيقية حيث عدد صحيح موجب حر من التربيع و عدد صحيح موجب فردي , وبشكل خاص سنبرهن أنه لاتوجد حقول رتبة زمرة صفوف تكافؤ ايديالاتها تساوي 1 وذلك في حالات خاصة . This work suggests studying the order of ideal class group of real quadratic fields with a square free integer number and an odd positive integer number ,especially we prove that there is no such fields with order of it’s ideal class group equal 1 , in special cases